If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6(6x + -15) = -9 Reorder the terms: 3x + -6(-15 + 6x) = -9 3x + (-15 * -6 + 6x * -6) = -9 3x + (90 + -36x) = -9 Reorder the terms: 90 + 3x + -36x = -9 Combine like terms: 3x + -36x = -33x 90 + -33x = -9 Solving 90 + -33x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + -33x = -9 + -90 Combine like terms: 90 + -90 = 0 0 + -33x = -9 + -90 -33x = -9 + -90 Combine like terms: -9 + -90 = -99 -33x = -99 Divide each side by '-33'. x = 3 Simplifying x = 3
| 5+x=-10+7 | | -4(5-x)+(3-x)(4-x)(5-X)-4(3-X)=0 | | -3.3x=-29.7 | | -182=6x-4(3x+29) | | ft(-4)=3x^2+7 | | 3-2(2x-4)=3x-4 | | x+.15x=1500 | | 0.6+7.9=4.6 | | f(x)=3x^2+7 | | 8x^2-53-21=0 | | 15x^2+25xy-45xz=0 | | x+x+23+23= | | 8a+5b=44 | | 4x+24=23 | | -5x+3(-6x+8)=-252 | | 10msquared= | | 3(2-3x)=2(-4x+7) | | exp(-0.1X^2)= | | 9/10-4/10= | | 2/5(x-9/40=3/10(7-2x) | | 2p+x+4p= | | 6x-(7+4x)= | | a^2(b-4)-25(b-4)=0 | | z=3x+9y | | -6y+x=5 | | 5/7x8/15 | | Y-6=-4(x+7) | | N^2-14n+69=-8 | | Ln(5x-8)=1 | | x=6x+5 | | 4x+37=100 | | 2v^2=15+7v |